Efforts to Increase Sales Results After the Covid-19 Pandemic (Case Study of Buket Umkm in Medan City) - Ami Radianti; Azizah Rahmah; Gita Aulyia Utami; Nadia Ulfa; Muhammad Taufiq Azhari (Penerbit Jurnal Indonesia, 2022)
The latest data obtained in early February 2022, the Medan City Cooperatives and SMEs Service said that the total MSMEs supervised by the Medan City Government were around 27,000 units out of a total of 70,000 units recorded. From the amount of data obtained, it is necessary to develop and expand target markets and boost economic growth for MSME actors in Medan City. The purpose of this research is to obtain information about efforts to increase sales of MSMEs in the city of Medan (bucket sales in the MMTC area) after the Covid-19 pandemic. In this study, the researcher used a qualitative method with a descriptive study. The main data source is obtained from interviews, then observations are marked by documentation. For supporting sources use previous studies. The results obtained by researchers are the need for a quick response from MSME actors and full support from the government to minimize the decline or loss caused during the Covid-19 Pandemic. MSME actors are also expected to be able to innovate and understand and understand the current digital world to encourage MSME actors to continue to grow and develop and be able to compete with other competitors.